2009
DOI: 10.1002/mrm.21970
|View full text |Cite
|
Sign up to set email alerts
|

Short echo spectroscopic imaging of the human brain at 7T using transceiver arrays

Abstract: Recent advances in magnet technology have enabled the construction of ultra high-field magnets (7T and higher) that can accommodate the human head and body. Despite the intrinsic advantages of performing spectroscopic imaging at 7T, increased SNR and spectral resolution, few studies have been reported to date. This limitation is largely due to increased power deposition and B1 inhomogeneity. To overcome these limitations, we have utilized an 8 channel transceiver array with a short TE (15 ms) spectroscopic ima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
111
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(114 citation statements)
references
References 23 publications
3
111
0
Order By: Relevance
“…As the coupling strength, which governs the overall width of a multiplet, is independent of the external magnetic field, the spectral resolution between coupled resonances is improved with increasing field strength (19)(20)(21)(36)(37)(38). Moreover, the multiplet pattern of the C4 proton resonances of Glu, Gln and GSH, which are strongly coupled to the C3 protons at low fields, is Figure 7.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…As the coupling strength, which governs the overall width of a multiplet, is independent of the external magnetic field, the spectral resolution between coupled resonances is improved with increasing field strength (19)(20)(21)(36)(37)(38). Moreover, the multiplet pattern of the C4 proton resonances of Glu, Gln and GSH, which are strongly coupled to the C3 protons at low fields, is Figure 7.…”
Section: Discussionmentioning
confidence: 92%
“…With these benefits, previous short-TE, single-voxel MRS (19,36) and spectroscopic imaging (20) studies have reported improved measurement of Gln and GSH by spectral fitting. It appears that the precise detection of Gln and GSH in the frontal brain using short TE at 7 T is challenging because of difficulties with B 0 shimming, the large width of the multiplets and the increased vulnerability to motion artifacts.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Magnetic field inhomogeneities result primarily from susceptibility differences between different tissues and between tissue and air cavities, which are scaled non-linearly in ultra-high magnetic fields [47]. Thus, voxels that are placed in inhomogeneous regions of the brain, such as the temporal poles, are difficult to shim due to their close proximity to the sinuses.…”
Section: Shimmingmentioning
confidence: 99%
“…The unsuppressed water signal was selected as the reference for computing the coil sensitivities and phase shifts of individual coil elements in this study (12)(13)(14)17,18,21), that is,…”
Section: Lðwþ5wmentioning
confidence: 99%